Technologies for the diagnosis of angle closure glaucoma (ACE): protocol of a prospective, multicentre, cross-sectional diagnostic study - Gianni Virgili; John G Lawrenson; Paul J Foster; Augusto Azuara-Blanco; Mike Clarke; Anthony J King; Ciaran O'Neill; Anish Jindal; Christopher R Cardwell; Meenakshi Sharma; Mary Guiney; Winnie Nolan (BMJ Open, 2023)
Introduction Angle-closure is responsible for half of all glaucoma blindness globally. Patients with suspected glaucoma require assessment of the drainage angle by an experienced clinician. The goal of this study is to evaluate the diagnostic performance and cost-effectiveness of two non-contact tests, anterior segment OCT (Optical Coherence Tomography) (AS-OCT) and limbal anterior chamber depth for patients referred to hospital with suspected angle closure compared with gonioscopy by ophthalmologist.Methods and analysis Study design: prospective, multicentre, cross-sectional diagnostic accuracy study. Inclusion criteria: adults referred from community optometry to hospital with suspected angle closure. Primary outcome: Sensitivity and specificity. Secondary outcomes: Positive/negative likelihood ratios, concordance, cost-effectiveness, proportion of patients requiring subsequent clinical assessment by ophthalmologist. Sample size: 600 individuals who have been referred with suspected angle closure from primary care (community optometry). We will have a 95% probability of detecting the true sensitivity of either test to within ±3.5% based on a sensitivity of 90%. The study would also have a 95% probability of detecting the true specificity of either test to within ±5%, assuming a specificity of 75%.Ethics and dissemination Ethical Review Board approval was obtained. REC reference: 22/LO/0885. Our findings will be disseminated to those involved in eye care services. We will have a knowledge exchange event at the end of the study, published via the Health Technology Assessment web page and in specialist journals. The results will be presented at professional conferences and directly to patients via patient group meetings and the Glaucoma UK charity.Trial registration number ISRCTN15115867.